AVAILABILITY AND DEGREE OF CONTAMINATION OF HEAVY METALS IN SOILS AND WATER OF BOMO AND GALMA IRRIGATION FARM LANDS, ZARIA,KADUNA STATE, NIGERIA - Nafiu, M. I.; Lawal, N.; Abdullahi, R. I.; Usman, L. U.; Yaya, A. A.; Habu, I. I. (FUDMA JOURNAL OF SCIENCES, 2023)
This research was designed to assess the level of heavy metal (Lead Pb and Cadmium Cd) and degree of contamination in soils and water located in Bomo and Galma irrigation farm lands. Soil and water samples collected from Bomo Lake, River Galma and borehole (serving as control) were digested and analyzed using Atomic absorption spectrophotometer to determine the heavy metal concentrations. The results showed that concentrations of Pb in soil located in Bomo ranges from 1.82 mg/kg to 6.19 mg/kg while Cd concentrations range from 0.03 mg/kg to 0.12 mg/kg. Pb concentrations in soil located in Galma ranges from 1.62 mg/kg to 4.03 mg/kg and Cd concentrations ranges from 0.02 mg/kg to 0.10 mg/kg. Concentrations of Pb in Bomo Lake ranges from 1.47 mg/kg to 3.09 mg/kg while Cd concentrations in Galma borehole water ranges from 0.02 mg/kg to 0.09 mg/kg. Pb concentrations in River Galma ranges from 1.14 mg/kg to 2.82 mg/kg while Cd concentrations in Galma borehole water ranges from 0.01 mg/kg to 0.08 mg/kg. Pollution Load Index (PLI) in Bomo ranges from 0.92 to 6.39 while in PLI in Galma ranges from 0.32 to 4.96. The study suggests that there are high concentrations of Pb than Cd in Soil and water and high PLI. This calls for intervention of the site quality in order to prevent or reduce the level of pollution as it could be moved up the food chain through bioaccumulation and magnification since these locations are popular for vegetable cultivation.
Keywords: Availability; Degree of Contamination; Contamination Factors; Heavy metals; Pollution Load Index.